South Meets South : Enriching the Development Menu - Maruri, Enrique (2012)
African countries, like Nigeria, with an emerging information technology (IT) industry, are examples of how globalization has opened up vast new opportunities. Information technology and business process outsourcing is a multibillion dollar talent-driven industry with a market that is still untapped. Africa is keen on exploring this new frontier which has the potential to create thousands of quality jobs for its young people. But to do so, it must nurture the right skills. Where can these be found?